Perlindungan Hukum Terhadap Pemegang Izin Pemakaian Tanah Aset Pemerintah Kota Surabaya: Ditinjau dari Hak dan Kewajiban - Suzana, Merillyn Victoria (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of land assets of the Surabaya City Government is important in the context of sustainable urban development. This land use permit gives certain parties the right to use land owned by the city government. However, permit holders also have certain obligations that must be complied with in accordance with applicable regulations. This article aims to examine the legal protection provided to holders of permits to use land assets of the Surabaya City Government, with a focus on the analysis of related rights and obligations. The research method used is normative legal research with reference to relevant legislation, as well as case studies related to the implementation of land use permits in Surabaya. The research results show that legal protection for land use permit holders includes important aspects such as clarity of land use rights, transparent permit obtaining procedures, and fair dispute resolution mechanisms. However, there are still challenges in implementation that require improving regulations and increasing legal awareness among permit holders. In conclusion, holders of permits to use land assets of the Surabaya City Government have adequate legal protection to exercise their rights, but further efforts are needed to ensure compliance with the obligations that have been determined. It is hoped that this article can contribute to further understanding of the dynamics of legal protection for the use of public land assets in Indonesia.